A Short History of Posterior Dynamic Stabilization - Cengiz Gomleksiz; Mehdi Sasani; Tunc Oktenoglu; Ali Fahir Ozer (Advances in Orthopedics)
Interspinous spacers were developed to treat local deformities such as degenerative spondylolisthesis. To treat patients with chronic instability, posterior pedicle fixation and rod-based dynamic stabilization systems were developed as alternatives to fusion surgeries. Dynamic stabilization is the future of spinal surgery, and in the near future, we will be able to see the development of new devices and surgical techniques to stabilize the spine. It is important to follow the development of these technologies and to gain experience using them. In this paper, we review the literature and discuss the dynamic systems, both past and present, used in the market to treat lumbar degeneration.